Study Abroad Objectives and Satisfaction of International Students in Japan - Hennings, Matthias; Tanabe, Shin (Journal of International Students, 2018)
Many Japanese universities have created short-term study abroad programs with the aim of offering a satisfying study abroad experience to international students. Based on a survey of 131 international students, this paper analyzes these students’ objectives and their relation to student satisfaction. As the results show, many students regard their experience of living in Japan as more important than their academic pursuits. Furthermore, for students with prior knowledge of Japanese, improving language skills tends to result in higher satisfaction, while for students who do not speak the local language, achieving cross-cultural skills is a major factor for having a satisfying experience.